Influence of vitamin D status on the severity of anemia of inflammation in young children with acute inflammatory bacterial respiratory diseases - Lezhenko, H. O.; Pogribna, A. O.; Леженко, Геннадій Олександрович; Погрібна, Анастасія Олександрівна (My University, 2021)
We have studied the effect of vitamin D status on the severity of anemia of inflammation in young children with acute inflammatory bacterial respiratory diseases. Some indicators of iron metabolism were analyzed depending on the level of vitamin D in the blood serum in the understanding the development of anemia of inflammation.
Keywords: anemia of inflammation; vitamin D; erythropoietin; ferritin; young children